Evaluating quality and impact of acute paediatric inpatient care: Defining the domains for a Person Centred Outcome Measure (PCOM) in children and young people admitted with self-harm or eating disorders - Manning, Joseph C.; Bean, Dorothy; Coad, Jane; Blake, Iszara; Bingham, Verity; Cooper, Joanne; Carter, Tim; Turner, Andrew; Hendron, Elizabeth; Rychwalska-Brown, Lucy; Wood, Damian; Latter, Karine (NHS England, 2015)
Background and purpose: In the United Kingdom, the prevalence of children and young people (CYP), up to the age of 18 years, accessing acute paediatric inpatient care with mental health problems is increasing, with self-harm and eating disorders particularly prevalent. This initial period of acute inpatient care can involve multiple assessments and interventions in order to meet physical, psychological and social needs. However, there is a distinct paucity of published literature reporting CYP service users’ experiences and outcomes of being in receipt of non-specialist inpatient care. Therefore this project aimed to undertake the preliminary work in developing a Person Centred Outcome Measure (PCOM) for this patient group by identifying the domains for a PCOM and establishing how such a measure could be implemented. Methods: A two phase sequential design was adopted which involved: (1) a rapid review of the literature and (2) an evaluation of experiences and outcomes through stakeholder engagement events with children and young people admitted with self-harm or eating disorders, their parents and carers, and professionals from health, social care and education. Findings: Rapid review of the literature • There is a lack of reported outcomes relating to CYP admitted to inpatient care with self-harm within the literature. • Outcomes reported by CYP appear to relate to aspects of care delivery, communication and the inpatient environment; • CYP reports predominantly relate to deficits in service provision which is recognised to negatively impact on experience and inhibit recovery and outcome. Findings: Stakeholder workshops • In total 96 CYP, parents and carers, and professionals participated in the stakeholder event. • Disparities in experiences and the implied quality of being in receipt of care were identified. • Synthesis of findings identified five domains that could be used to develop a PCOM that included: Privacy and surveillance; Receiving holistic care; Making choices and being understood through timely, relevant and appropriate communication; Working together to plan and achieve care goals; and Respect and empowerment • Variation was evident between CYP stakeholders as to the acceptability of when and how outcomes are measured. Conclusion: Findings from this project provide the foundations for a PCOM for CYP admitted to acute paediatric care with self harm or eating disorders to be developed, tested, implemented and evaluated. The domains identified have the potential to be further developed and validated as an instrument with a larger and more diverse sample of CYP.